Hepatic angiosarcoma: Pitfalls in establishing a diagnosis. (September 2021) - Flabouris, Katerina; McKeen, Suzanne; Chaves Gomes, Deborah; Chaudhuri, Debajyoti; Russell, Patrick
Hepatic angiosarcomas are rare, deceptive and aggressive malignancies that remain notoriously difficult to diagnose and treat. This case report discusses some of the common challenges faced by clinicians, and potential clinical, radiological and histological clues to this often elusive diagnosis.